Swainsonine Triggers Paraptosis via ER Stress and MAPK Signaling Pathway in Rat Primary Renal Tubular Epithelial Cells - Wang, Shuai; Guo, Yazhou; Yang, Chen; Huang, Ruijie; Wen, Yuting; Zhang, Chunyan; Wu, Chenchen; Zhao, Baoyu (Frontiers in Pharmacology, 2021)
Swainsonine (SW), an indolizidine alkaloid extracted from locoweeds, was shown toxic effects in multiple studies, but the underlying action mechanism remains unclear. Here, we show that SW induces rat primary renal tubular epithelial cells (RTECs) death accompanied by vacuolation in vitro. The fluorescence with the endoplasmic reticulum (ER)-Tracker Red and transmission electron microscopy results indicated that the vacuoles were of ER origin, typical of paraptosis. The level of ER stress markers, such as polyubiquitinated proteins, Bip, CHOP and cytoplasmic concentration of calcium have drastically increased. Interestingly, autophagy inhibitors could not interrupt but enhance the induction of cytoplasmic vacuolization. Furthermore, MAPK pathways were activated by SW and inhibitors of ERK and JNK pathways could prevent the formation of cytoplasmic vacuolization. SW is known to cause autophagy and apoptosis, but there has been no report on paraptosis mediated cell death. In this study, we confirmed that SW induces cell paraptosis through ER stress and MAPK signaling pathway, thus further laying a theoretical foundation for the study of SW toxicity mechanism.